Patient Engagement. A Consumer-Centered Model to Innovate Healthcare - Graffigna, Guendalina (De Gruyter, 2015)
Patient engagement should be envisaged as a key priority today to innovate healthcare services delivery and to make it more effective and sustainable. The experience of engagement is a key qualifier of the exchange between the demand (i.e. citizens/patients) and the supply process of healthcare services. To understand and detect the strategic levers that sustain a good quality of patients' engagement may thus allow not only to improve clinical outcomes, but also to increase patients' satisfaction and to reduce the organizational costs of the delivery of services. By assuming a relational marketing perspective, the book offers practical insights about the developmental process of patients' engagement, by suggesting concrete tools for assessing the levels of patients' engagement and strategies to sustain it. Crucial resources to implement these strategies are also the new technologies that should be (1) implemented according to precise guidelines and (2) designed according to a user-centered design process. Furthermore, the book describes possible fields of patients' engagement application by describing the best practices and experiences matured in different fields.